Chapter Commodification o giustizia ambientale? I PES come strumento di governance del valore della natura - MARINO, DAVIDE (Territori, 2020)
Having defined the fundamental concepts related to the debate on ecosystem services within the framework of Socio-Ecological Systems, and starting from a critique of GDP and traditional accounting systems, new tools and methodologies functional to measuring the well-being and wealth of society are illustrated, which include the accounting of natural capital and associated ecosystem services. The PES (Payments for Ecosystem Services) tool is studied in detail and the possibility of using it for territorial rebalancing and social justice purposes is analysed.